2017
DOI: 10.1242/dev.137315
|View full text |Cite
|
Sign up to set email alerts
|

Folate receptor 1 is necessary for neural plate cell apical constriction during Xenopus neural tube formation

Abstract: Folate supplementation prevents up to 70% of neural tube defects (NTDs), which result from a failure of neural tube closure during embryogenesis. The elucidation of the mechanisms underlying folate action has been challenging. This study introduces Xenopus laevis as a model to determine the cellular and molecular mechanisms involved in folate action during neural tube formation. We show that knockdown of folate receptor 1 (Folr1; also known as FRα) impairs neural tube formation and leads to NTDs. Folr1 knockdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 76 publications
2
29
0
Order By: Relevance
“…On the other hand, in other vertebrates like Xenopus laevis , the necessity for cell divisions during neural tube formation has been ruled out by demonstrating that blocking DNA synthesis does not interfere with neurulation (Harris and Hartenstein, ). Nevertheless, folate action is necessary during Xenopus laevis neural tube formation, as recently demonstrated by our study (Balashova et al, ), suggesting that folate might play additional functions during neural tube formation besides its role as a vitamin for DNA synthesis. Moreover, many knockout mice for enzymes directly involved in folate metabolism did not exhibit increases in NTD incidence (Watanabe et al, ; Chen et al, ; Swanson et al, ).…”
Section: Introductionsupporting
confidence: 77%
“…On the other hand, in other vertebrates like Xenopus laevis , the necessity for cell divisions during neural tube formation has been ruled out by demonstrating that blocking DNA synthesis does not interfere with neurulation (Harris and Hartenstein, ). Nevertheless, folate action is necessary during Xenopus laevis neural tube formation, as recently demonstrated by our study (Balashova et al, ), suggesting that folate might play additional functions during neural tube formation besides its role as a vitamin for DNA synthesis. Moreover, many knockout mice for enzymes directly involved in folate metabolism did not exhibit increases in NTD incidence (Watanabe et al, ; Chen et al, ; Swanson et al, ).…”
Section: Introductionsupporting
confidence: 77%
“…In this light, it is notable that there is evidence that Folr1 can also function as a transcription factor in mammalian cells, with a large number of developmentally important genes as its target [ 213 ]. Furthermore, recent observations in Xenopus have pointed to a novel mechanism for the role of Folr1 and folate in neural tube closure [ 214 ]. Knockdown of Folr1 during neurulation in Xenopus causes failure to develop a neural tube.…”
Section: Folate and Ntdmentioning
confidence: 99%
“…Molecular mechanisms underlying this seemingly bi-directional interaction are a matter for future work, but our ndings reveal a dynamic interplay between PCP, microtubules and actomyosin in the mammalian neuroepithelium. It has been suggested that promotion of apical constriction is one of the bene cial consequences of folate which may contribute to its ability to prevent a proportion of human NT defects 92,93 . These interactions may therefore be speci cally disrupted in patients with mosaic PCP mutations and may identify more widely-applicable therapeutic targets.…”
Section: Resulting Apical Constriction Of Neuroepithelial Cells Requimentioning
confidence: 99%